Children's Empathy Attitude in The Storybook “Kue Kimu” By Lia Herliana And Ratu Wulan - Saidah, Kuni (International Proceedings of Nusantara Raya, 2024)
One of the emotional intelligences of a person is empathy, which is the ability to understand the suffering of others and to understand the opinions and feelings of others. Setting a good example and showing tolerance are important components of parenting strategies that aim to help children develop empathy. Parents should show empathy so that their children can learn from their example. Reading children's storybooks is one way to instill empathy in children, a trait that needs to be cultivated from an early age. This is because reading storybooks can stimulate children's many senses and help them become more socially intelligent. The type of research used in this study is library research. In this study, researchers used a qualitative approach which is a non-numerical data-based approach or using manuscript documents with existing thoughts. After the researchers analyzed the storybook "Kue Kimu", the attitude of children's empathy that is most visible in the storybook is Kimu's caring attitude towards his friend, Nara, who is absent from school due to illness. The storybook entitled "Kue Kimu" can be a reading material to be read and to teach empathy values by sharing, caring, compassion and there is also the value of children's creativity in the book. Reading storybooks can also improve children's interpersonal intelligence.